Well-being and the complexity of poverty: A subjective well-being approach - Mariano Rojas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This investigation studies human well-being from a subjective well-being approach. On the basis of a Mexican database the investigation shows that there is a weak relationship between subjective well-being and indicators of well-being such as income and consumption. Therefore, subjective well-being provides additional useful information to study human well-being and, in consequence, poverty. Three reasons for the existence of a weak relationship are studied: First, the fact that a person is much more than a consumer; second, the role of heterogeneity in human perceptions; and third, the existence of heterogeneity in purposes of life. The understanding and abatement of poverty would be better served by a concept of human well-being which incorporates subjective well-being indicators and which is based on the wholeness and complexity of human beings.
Keywords: I31; I32; J10; 330; socioeconomic indicators; subjective well-being; happiness; poverty; Lebensqualität; Sozialer Indikator; Mexiko